MULTIFUNCTIONAL NANOSTRUCTURES FORMED OF GOLD OR SILVER NANOPARTICLES AND DIFFERENT BIOMOLECULES WITH MEDICAL APPLICATIONS - TOMOAIA-COTIŞEL, Maria (2016)
This monography presents an overview of our recent developments[141], mainly from the laboratories of Physical Chemistry Center, Department of Chemical Engineering, Faculty of Chemistry and Chemical Engineering, Babes-Bolyai University of Cluj-Napoca, in the field of multifunctional nanostructures formed of gold or silver nanoparticles and different biomolecules along with their potential medical applications in nanomedicine. In addition, collaborative research was done in various other laboratories of authors engaged in this research as partners, and are indicated in the original research articles and patents, cited as reference.